Raising effective awareness for circular economy and sustainability concepts through students' involvement in a virtual enterprise - Keramitsoglou, Kiriaki; Litseselidis, Theodoros; Kardimaki, Anna (Frontiers in Sustainability, 2023)
Despite the increased research concerning the transition of the well-established linear-oriented economic system towards the circular economy (CE) model, the existing literature on adopting and implementing educational approaches reinforcing the CE concept in secondary education seems limited. In light of the current challenges and the critical role of education to empower students to explore new paths of sustainable development and grow into active citizens, conscious producers, and consumers, this contribution looks into experiential learning as an effective tool for teaching CE and sustainability concepts. The literature review has revealed a research gap as regards the formulation of educational approaches to effectively support CE concepts for secondary education students, particularly in Greek vocational education. The paper describes and critically discusses how a virtual enterprise could introduce secondary-level students to the circularity and sustainability perspective, prepare them to build prosperity, and act circularly in the future. Drawing on the activities of thirty-two students coming from different disciplines and participants in a virtual agri-business, we recommend practical educational strategies hoping (i) to encourage teachers to adopt innovative teaching methods and share good practices of the CE teaching and (ii) to urge education policymakers to integrate the CE vision into school curricula. Furthermore, the students' responses to a structured questionnaire before and after the programme implementation indicates that experiential learning should be supported by the teaching of theoretical aspects for the better consolidation of abstract concepts such as CE and sustainability. The implementation of a circular enterprise by a student team consists of a positive prospect for the community and economy.